STUDI KOMPARATIF METODE CIRC DENGAN KWL UNTUKMENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMANPESERTA DIDIK FASE B SEKOLAH DASAR - Fitrianti Nur Indah Sari; Rina Heryani; Non Dwishiera Cahya Anasta (JRPD (Jurnal Riset Pendidikan Dasar), 2025)
This study was motivated by the low reading comprehension skills of fourth-grade students in phase B, who still have difficulty understanding the content of reading materials, thus necessitating measures to improve their reading comprehension skills. There are two methods that can improve reading comprehension skills, namely the CIRC (Cooperative Integrated Reading and Composition) method and the KWL (Know, Want, Learn) method. The purpose of this study to determine the difference in reading comprehension skills between fourth-grade students in phase B who use the CIRC learning method and those who use the KWL learning method. The research method used is a quantitative approach with a quasi-experimental design and a nonequivalent pretest-posttest control group design. The data analysis techniques used are the mean difference test and the N-Gain test. The research results obtained data showing that there were differences in the pretest results of reading comprehension skills between the two fourth-grade classes. Furthermore, the posttest results indicated that the two classes had differences in the three indicators: identifying the main idea, retelling, and drawing conclusions. Based on the N-Gain difference score test, students who used the CIRC learning method experienced a more significant increase of 98.16% with a fairly effective category compared to students who used the KWL method with an ineffective category.